Through the Looking Glass: Transparency about Others' Luck and Effort Enhances Redistribution - Juliane V. Wiese; Nattavudh Powdthavee; Jonathan Yeo; Yohanes E. Riyanto (Institute of Labor Economics (IZA), 2023)
How do we persuade people to part with money they feel they have rightly earned? We conducted a dyadic experiment (N=1,986) where luck determined which of the players' performance counted toward winning the game. Despite luck playing a large part, we found strong evidence of justified deservingness among the winners. The better they performed in the task, the less they redistributed to their nonwinning partner. However, in treatments where performance was transparent, winners significantly increased redistribution to nonwinners who performed similarly well. We find that transparency can effectively alter redistributive preferences even when people feel fully deserving of their income.
Keywords: C9; D9; 330; luck; efforts; survivalship bias; redistribution; inequality; deservingness